The Effects of Acute Ketone Monoester Supplementation on Exercise Efficiency and the Influence of Dose and Intensity - Bone, Jack (My University, 2023)
Introduction: Acute ketone monoester (KE) supplementation affects exercise responses but there are equivocal data regarding the effects on exercise efficiency. We examined the effect of ketone monoester ingestion on exercise efficiency during cycling and probed further the influence of supplement dose and exercise intensity. This study was registered prior to data collection at ClinicalTrials.org (NCT05665855). Methods: Twenty-eight trained adults were recruited [16 males, 12 females; peak oxygen uptake (V̇O2peak): 59±11 ml·kg-1·min-1]. Participants completed three experimental trials in a randomized, crossover, and double-blinded manner, each separated by ~1 week. Participants ingested either a 0.3 (KE-LO) or 0.6 g/kg (KE-HI) body mass dose of KE or a flavour-matched placebo (PLAC) ~30 min prior to exercise. The incremental cycling protocol involved a 3-minute warm-up, three 5-minute stages at 75%, 100%, and 125% of individual ventilatory threshold, and a ramp increase to volitional exhaustion. Expired gases and heart rate were measured continually during exercise. Results: Venous blood [ß-hydroxybutyrate], the major circulating ketone body, was higher in both KE conditions compared to PLAC and also different between conditions (3.0±1.1 and 2.3±0.6 vs 0.2±0.1 mM; all p<0.05). There were no differences in submaximal exercise V̇O2, exercise economy, gross efficiency, or delta efficiency between conditions (all p>0.05). Submaximal exercise heart rate and ventilation were higher in both KE conditions compared to PLAC (141±11 and 141±12 vs 137±12 beats/min; 63±14 and 62±13 vs 60±13 L/min, respectively; all p<0.05). Peak power output at V̇O2peak was lower in KE-HI compared to both KE-LO and PLAC (329±60 vs 339±62 and 341±61 W; both p<0.05). Conclusion: KE supplementation did not alter exercise efficiency during submaximal cycling. KE ingestion increased cardiorespiratory stress during submaximal exercise and the higher dose reduced peak aerobic power output. Future studies should investigate the mechanisms by which KE ingestion alters exercise responses.
Keywords: Exercise efficiency; Metabolism; Ketone Supplement; Maximal oxygen uptake